Przesłanki i zasady odpowiedzialności prawnej w działalności reklamowej - Płachta, Michał (Wydział Prawa i Administracji UAM, 1990)
Polish legislation does not contain the act which would comprehenisively regulate numerous and diversified problems connected with advertising activity. The author distinguishes the following grounds of legal regulation of advertising activity: 1) general principles of law and legislation, principles of social co- -existence and constitutional norms; 2) norms contained in particular branches of law, e.g. in civil, penal and copyright law, wich may find application in advertising activity; 3) provisions enacted specifically for advertising activity. Besides, three interdictions should be observed in advertising activity: an interdiction to infringe law, to infringe accepted customs and an interdiction to disinform. The author rejects the presumption according to which each advertising act (irrespective of accompanying circumstances) is to express the advertiser's will be conclude the contract of sale. Otherwise, the advertiser were always bound to conclude such a contract under the sanction of civil-law liability. The Polish legislator regulates legal character of advertising acts in 2 provisions. One of them protects the interests of advertising enterprises (Art. 71 of the Civil Code), while the other protects the interests of consumers (Art. 543 of the Civil Code). According to Art. 71, announcements, advertisement, price-lists and other information addressed to the public or to particular persons are, in case of doubt, not to be considered an offer but an invitation to negotiations. In turn, according to Art. 543, placing a priced thing on public display is to be considered and offer to sale.
Conditions and principles of liability i n advertising activity